First record of the rare stenopodidean shrimp Odontozona spongicola (Alcock & Anderson, 1899) (Decapoda: Stenopodidea: Stenopodidae) from Indonesia - Chen, Chien-Lin; Chan, Tin-Yam (Zootaxa, 2021)
The stenopodidean shrimp Odontozona spongicola (Alcock & Anderson, 1899) collected by the South Java Deep-Sea Biodiversity Expedition 2018 (SJADES 2018) is a new record from Indonesia. The specimen of O. spongicola recently listed from the South China Sea is also formally reported here in. The characteristcs and coloration of this rare species are described and illustrated.